Absensi Karyawan menggunakan Deteksi Wajah dan Gerakan Tangan Berbasis Raspberry Pi - Helfy Susilawati (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
Keeping attendance is an activity that must done by employees. Attendance is usually collected by using selfie photos, yet this method still can be manipulated by the employees by sticking their selfie photos at work to make it look like they come to work. An alternative to overcome the issue is by involving the employee’s hand gestures. The employee’s attendance is recorded once his/her face is detected, and he/she makes hand gestures following the previously registered codes. The hand gestures indicate that there are humans onsite. The system was built using the prototype method, using Haar Cascade and Local Binary Pattern Histogram to detect faces and hand gestures. The results showed that the system can recognize faces according to its user ID and can detect finger codes based on the hand gestures. The recapitulation of arrival and departure hours from work is stored in the .xls. extension file